Legal Aspect of Teleradiology at Hospital in Fulfillment of Patient Right - Adrian Benhard Mardi Putra; Trihoni Nalesti Dewi; Daniel Budi Wibowo (SOEPRA, 2018)
The geographical situation and the disparity of the radiologist distribution make access to radiology services in rural, remote and island areas unmet. The presence of teleradiology can eliminate such gaps by increasing the speed and accuracy of diagnoses through technological assistance carried out in stages through the regulation of the telemedicine pilot project. Although teleradiology is currently still limited to trials, it is necessary to consider legal aspects, such as fairness, usefulness and legal certainty to the fulfillment of patient rights.This study is sociological-juridical with explanatory research specification. This study uses primary data obtained from in-depth interview to 6 informants consisting of 1 region head IDI, one head of medical support head, 1 ICT legal expert, with one radiologist with two radiographers who is performing teleradiology. Meanwhile, secondary data as media supporting obtained through by literature and legislation review. Furthermore, data obtained are processed and analyzed qualitatively. Based on the results of research in dr. Wahidin Sudirohusodo Makassar Hospital and H.A. Sulthan Daeng Radja Bulukumba Hospital, the implementation of teleradiology in both hospitals resulted in some of the patient's rights being unfulfilled due to infrastructure constraints, limited human resources and lack of socialization. Patients are not entitled to informed consent and the provision of medical information. The right to the second opinion is also not fulfilled so that the patient does not get a chance to seek a second chance on the diagnosis of his illness.  The non-fulfillment of both rights also affects the right to patient safety in the hospital in the case of management and taking action due to incomplete medical record data. As for the legal aspects to be achieved in the implementation of teleradiology, i.e., equity, usefulness, and legal certitude aspect.  However, from these three aspects, the legal certitude aspect is not implemented properly as part of the fulfillment of patient rights due to existing regulations not to set certain things that can provide legal protection for provider or recipient of teleradiology service.